Chemical composition and biological activity of essential oil of Nepeta pannonica - Kurmantayeva, G.K.; Marchenko, A.B.; Ivasenko, S.A.; Seidakhmetova, R.B.; Smagulov, M.K.; Atazhanova, G.A. (KU Publ., 2021)
Search for new sources of biologically active substances from plants of local flora is a promising area of modern phytochemical science. The article examines the composition of essential oil samples obtained from Nepeta pannonica, growing in the Karaganda region with the use of gas-chromatography-mass spectrometry method. The differences in the chemical composition of the oil depending by the plant organs have been identified. The main component of essential oil is nepetalactone. For the analysis, a unified method for determining the component composition of essential oils, as well as an Agilent Technologies 7890A chromatograph system with a 5975C inert MSD mass spectrometric detector were used. According to the data, the following substances were identified in the essential oils of the plant — 1,8-cineole, nepetalactone, germacrene D, screening of essential oil of Nepeta pannonica for antimicrobial and analgesic activity. Keywords: Nepeta pannonica, essential oil, gas-chromatography-mass spectrometry, chemical
Nepeta pannonica эфир майының химиялық құрамы және биологиялық белсенділігі
Химический состав и биологическая активность эфирного масла Nepeta pannonica
Keywords: essential oil; gas-chromatography-mass spectrometry; chemical composition; antimicrobial and analgesic activity